Foot Arch and Plantar Pressure in the Age of 17-21 Years - Arif Wicaksono; Sasanthy Kusumaningtyas; Angela BM Tulaar (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Research on the plantar segment has not been widely carried out in Indonesia’s population, even though the plantar segment data will be essential in further research and therapy of plantar-related problems. Therefore, this research intends to describe the plantar profile: the foot arch and the plantar pressure difference between the right and left foot. This research applied a cross-sectional study. Subjects were recruited from the Faculty of Medicine students, Universitas Indonesia, class 2012, with inclusion criteria aged 17-21 years and normal gait. Meanwhile, the exclusion criteria consisted of having postural abnormalities, a history of neuromusculoskeletal disorders in the lower limbs, a history of fractures in the spine and legs, a history of surgery on the spine and legs, and refusing to participate in the study. Research subjects stood on a plantar scanner, conducted at the Anatomy Laboratory, the Faculty of Medicine, Universitas Indonesia. The Mann-Whitney test was then used to analyze the difference in plantar pressure between the right and left foot. The results revealed that a hundred research subjects had a proportion of a low foot arch of 4%, a normal foot arch of 89%, and a high foot arch of 7%. The median right plantar pressure was 273.5 KPa, while the median left plantar pressure was 253.5 KPa. The Mann-Whitney test showed a p-value of 0.954 for the pressure difference between right and left foot. There was no plantar pressure difference between the right and left foot.